Use of Computer Decision Support in an Antimicrobial Stewardship Program (ASP) - Evans, R.S.; Olson, J.A.; Stenehjem, E.; Buckel, W.R.; Thorell, E.A.; Howe, S.; Wu, X.; Jones, P.S.; Lloyd, J.F. (Applied Clinical Informatics, 2015)
Objective: Document information needs, gaps within the current electronic applications and reports, and workflow interruptions requiring manual information searches that decreased the ability of our antimicrobial stewardship program (ASP) at Intermountain Healthcare (IH) to prospectively audit and provide feedback to clinicians to improve antimicrobial use.Methods: A framework was used to provide access to patient information contained in the electronic medical record, the enterprise-wide data warehouse, the data-driven alert file and the enterprise-wide encounter file to generate alerts and reports via pagers, emails and through the Centers for Diseases and Control’s National Healthcare Surveillance Network.Results: Four new applications were developed and used by ASPs at Intermountain Medical Center (IMC) and Primary Children’s Hospital (PCH) based on the design and input from the pharmacists and infectious diseases physicians and the new Center for Diseases Control and Prevention/ National Healthcare Safety Network (NHSN) antibiotic utilization specifications. Data from IMC and PCH now show a general decrease in the use of drugs initially targeted by the ASP at both facilities.Conclusions: To be effective, ASPs need an enormous amount of “timely” information. Members of the ASP at IH report these new applications help them improve antibiotic use by allowing efficient, timely review and effective prioritization of patients receiving antimicrobials in order to optimize patient care.Citation: Evans RS, Olson JA, Stenehjem E, Buckel WR, Thorell EA, Howe S, Wu X, Jones PS, Lloyd JF. Use of computer decision support in an antimicrobial stewardship program (ASP). Appl Clin Inf 2015; 6: 120–135http://dx.doi.org/10.4338/ACI-2014-11-RA-0102
Keywords: Clinical decision support; antimicrobial stewardship; antibiotic resistance; patient specific alerts; antimicrobial stewardship program; ASP; medical informatics; computer decision support